Materials sealing preventing biofilm formation in implant/ abutment joints: Which is the most effective? A systematic review and meta-analysis - de Sousa, Cecília Alves [UNESP]; Taborda, Maria Beatriz Bello [UNESP]; Momesso, Gustavo Antônio Correa [UNESP]; Rocha, Eduardo Passos [UNESP]; dos Santos, Paulo Henrique [UNESP]; Santiago-Júnior, Joel Ferreira; Assunção, Wirley Gonçalves [UNESP] (American Academy of Implant Dentistry, 2020)
The purpose of this systematic review was to evaluate the literature available for materials exhibiting the best efficacy in preventing biofilm formation in the interior of implants. We searched PubMed/MEDLINE, Scopus, and Cochrane databases. This review is registered with the PROSPERO database and followed the suitability of the PRISMA protocol. The initial search resulted in 326 articles from the databases. After they were read, 8 articles remained, and the inclusion and exclusion criteria were applied. Six of these 8 articles were classified as in vitro and 2 were classified as in situ. The regions of the implants evaluated ranged from the interface of the pieces to the occlusal upper access of the abutment. The implant connections evaluated the Morse taper, external connection, and internal connection. Meta-analysis of the quantitative data was performed at a significance level of .05. Cotton exhibited poor control of infiltration, even in combination with other materials. Isolated gutta-percha (GP) and polytetrafluoroethylene (PTFE) tape with composite resin (CR) or GP performed better as physical barriers. The best results for chemical barriers were observed by the application of 1% chlorhexidine gluconate (CG) gel, thymol varnish, and the deposition of Ag films onto the surface. The applied meta-analysis did not show a significant difference in comparison between the different types of implant connections (P . .05). The application of CG and thymol varnish antimicrobials was effective in preventing biofilm formation and easy clinical execution; these could be used in combination with CR, GP, and PTFE.
Keywords: Bacterial leakage; Biofilms; Implant-abutment interface